2019
DOI: 10.1111/ped.13988
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with traditional medicines for perianal abscess in children

Abstract: Background: Combination therapy with two different traditional medicine formulations called hainosankyuto and juzentaihoto (TJ-122 and TJ-48; Tsumura & Co, Tokyo, Japan) may be effective for perianal abscess (PA), but their effectiveness has not been established. The present study investigated the effectiveness of combination therapy with TJ-122 and TJ-48 as the most effective conservative treatment for PA. Methods: We identified 69 patients with PA under 2 years of age and divided them into four groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Remarkably, in the present study, 6.5% (9/138) of patients developed new abscesses on the contralateral side of the anus. Several studies have previously reported a similar phenomenon (16,21,25,35,36), but the reason was unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Remarkably, in the present study, 6.5% (9/138) of patients developed new abscesses on the contralateral side of the anus. Several studies have previously reported a similar phenomenon (16,21,25,35,36), but the reason was unknown.…”
Section: Discussionmentioning
confidence: 94%
“…It has traditionally been treated surgically by incision and drainage (ID) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, in the past two decades, some studies have shown that the conservative management appears to be effective in selected cases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, the other studies have recommended that the surgical procedure should involve a careful identification for the fistula and treatment of that by fistulotomy (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the abscess ulcers during the treatment, it can heal naturally without scarring. 32 In traditional Chinese medicine, Qingreliangxue ointment was used to treat the perianal abscess of infants, which proved that it had a good effect of effectively reducing swelling and analgesia and the local skin temperature of the abscess. 33…”
Section: Treatment Conservative Treatmentmentioning
confidence: 99%
“…Discussions in the medical fraternity continue to center around the management of PA in children. Both conservative treatment and surgical treatment have been reported with good outcomes ( 2 , 4 , 6 , 8 , 10 , 12 , 25 ). Surgery must be performed when an abscess is likely to spread or shows no sign of spontaneous perforation ( 4 ).…”
Section: Discussionmentioning
confidence: 99%